PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN METODE PEMBELAJARAN GUIDE WRITING DI KELAS IV SDN 2 SIJUNJUNG KABUPATEN SIJUNJUNG - Amanda, Ginny; Sukma, Elfia; Chandra; Suriani, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the results of students' descriptive text writing skills which are still relatively low. This occurs because (1) students have difficulty in expressing ideas and concepts in writing descriptive texts, (2) students have not been able to describe objects in detail and concretely according to their characteristics (3) writing is not in accordance with the correct structure (4) writing EYD is not yet correct, (5) word choice is less appropriate and still limited. The purpose of this study is to describe the improvement in the results of descriptive text writing skills using the guide writing learning method in class IV SDN 2 Sijunjung Sijunjung Regency. This research is a Classroom Action Research (CAR) using quantitative and qualitative approaches. The subjects of this study were teachers and students in class IV SDN 2 Sijunjung Sijunjung Regency totaling 23 people. The results of this study show an improvement in: (1) the suitability of the contents of the descriptive essay to the topic, (2) structure, (3) word choice, (4) object details, (5) mechanics. Based on the research results, each indicator assessment in cycles I and II has increased after the implementation of the guide writing learning method in grade IV of SDN 2 Sijunjung, Sijunjung Regency. Therefore, it can be concluded that the guide wrsiting learning method can improve the descriptive text writing skills of grade IV in elementary schools.